Réponses

2014-03-18T15:10:43+01:00

Ex1 résultat sous forme la plus simple possible  : par convention, x =*
A: 3/7x(7/3-5/6)

A = 3/7 * (14/6-5/6)

A = 3/7 * 9/6

A =3/7*3/2

A =9/14

B= 3/7x7/3-5/6

B = 1 - 5/6

B = 1/6
C:12x(1/3-1/6)

C = 12 * 1/6

C = 2
D:12x1/3-1/6

D = 4 - 1/6

D = 24/6 - 1/6

D = 23/6


ex2:calcul d'une expression 
a.                  B.                   A+b.            A-b.          Axb
11/9.           7/9.                  18/9              4/9            77/81

3/4.              3/16.               15/16             9/16           9/64